PENGARUH DUKUNGAN SOSIAL TERHADAP PRESTASI AKADEMIS MELALUI MOTIVASI BELAJAR SEBAGAI INTERVENING PADA MAHASISWA YANG MERANTAU (STUDI KASUS PADA MAHASISWA FEB UNIVERSITAS TANJUNGPURA) - admin, Kristina Risea Anggia B1021161019 (Jurnal Manajemen Update, 2021)
ABSTRACTThe purpose of this study was to determine the effect of social support on academic achievement through learning motivation as an intervening student who migrated to the Faculty of Economics and Business, Tanjungpura University. The data used in this study are primary data. The data collection method was done by distributing written questions in the form of questionnaires to respondents. The population used in this study were students who had migrated to the Faculty of Economics and Business, Tanjungpura University in batch 2017 & 2018. The research sample was selected using simple random sampling technique and the sample obtained was 90 respondents. The data analysis model used is path analysis.The results in this study indicate that (1) social support had a significant effect on the learning motivation of overseas student FEB Untan, (2) social support had a significant effect on the academic achievement of oversea students FEB Untan, (3) learning motivation had a significant effect on the academic achievement of students who had left FEB Untan, (4) learning motivation as an intervening social support on academic achievement of overseas students FEB Untan has a significant effect but at a low level.Keywords: Social Support, Learning Motivation, and Academic Achievement. Referensi Atnafu, M. (2012). Motivation, Social Support, Alienation from the School and their Impact on Student’s Achievement in Mathematics: The Case of Tenth Grade Student. Ethiopian Journal of Education and Sciences. 8(1). 53-74.Christiani, P. (2016). Pengaruh Budaya Sekolah dan Dukungan Orangtua Terhadap Prestasi Belajar Mata Pelajaran IPS Siswa Kelas VII di SMP Negeri 2 Kota Probolinggo. Jurnal Penelitian dan Pendidikan IPS. 10(1), 76-89.Cirik, I. (2016). Relationships between Social Support, Motivation, and Science Achievement: Structural Equation Modeling. Anthropologist. 20(12). 232-242.Dennis, J. M., Phinney, J. S., & Chuateco, L. I. (2005). The Role of Motivation, Parental Support, and Peer Suport in the Academic Success of Ethnic Minority First-Generation College Student. Journal of College Student Development. 46(3). 223-236-Darmawati, J. (2013). Pengaruh Motivasi Belajar dan Gaya Belajar Terhadap Prestasi Belajar Ekonomi Siswa SMA Negeri di Kota Tuban. Jurnal Ekonomi Pendidikan dan Kewirausahaan. 1(1). 79-90.Darojah, N. R., & Hadijah, H. S. (2016). Analisis Pengaruh Kompetensi Kepribadian Guru dengan Motivasi Belajar sebagai Variabel Intervening terhadap Prestasi Belajar Siswa Kelas X Administrasi Perkantoran. Jurnal Pendidikan Manajemen Perkantoran. 1(1). 109-118.Emeralda, G. N., & Kristiana, I. F. (2017). Hubungan Antara Dukungan Sosial Orang Tua Dengan Motivasi Belajar Pada Siswa Sekolah Menengah Pertama. Jurnal Empati, 7 (3), 154-159.Feng, H. Y., Fan, J. J., & Yang, H. Z. (2013). The Realitionship of Learning Motivation and Achievement in ELF: Gender as an Intermeted Variabel Educational Research International. 2(2).Fitriyani, N. (2019). Pengaruh Dukungan Sosial dan Psychological Well Being terhadap Prestasi Belajar Santri Kelas X. LITERASI, 10 (1).Handayani, D. (2018). Dukungan Sosial dan Adaptasi Kehidupan Kampus pada Mahasiswa Perantau (Tesis yang tidak dipublikasikan), Universitas Islam, Indonesia.Hamdu, G., & Agustina, L. (2011). Pengaruh Motivasi Belajar Siswa Terhadap Prestasi Belajar IPA di Sekolah Dasar. Jurnal Penelitian Pendidikan. 12(1). 81-86.Lestari, S. (2018). Peran Teknologi Dalam Pendidikan di Era Globalisasi. Jurnal Pendidikan Agama Islam. 12(2). 94-100.Mansyur, M. M. (2015). Hubungan Lingkungan Sosial Terhadap Motivasi Belajar Peserta Didik di Pondok Pesantren Darul Arqam Muhammadiyah Gombara Sulawesi Selatan (Tesis yang tidak dipublikasikan), Fakultas Tarbiyah dan Keguruan Uin Alauddin Makassar, Indonesia.Marfiyanto, T., & Rodiyah, S. K. (2018). Studi Tentang Prestasi Belajar Siswa dalam Berbagai Aspek dan Faktor yang Mempengaruhi. Jurnal Komunikasi Pendidikan. 2(2). 115-123.Mauliddya, S. A., & Rustam, A. (2019). Peran Dukungan Sosial Orang Tua terhadap Prestasi Akademis melalui Mediasi Motivasi Belajar Intrinsik. Gadjah Mada Journal of Psychology. 5(2). 166-177.Nursiwanti, T. (2016). Hubungan Antara Dukungan Sosial dan Kedisiplinan dengan Motivasi Belajar pada Siswa/I SMA Negeri 1 Hamparan Perak (Tesis yang tidak dipublikasikan), Universitas Medan Area, Indonesia.Oktasari, M., Solihatum., & Monalisa. (2018). Konstribusi Dukungan Sosial Teman Sebaya Terhadap Motivasi Berprestasi Siswa. Kajian Konseling dan Pendidikan, 1 (1), 22-28.Prasetyo, A. N., & Kusumantoro. (2015). Pengaruh Kompetensi Pedagogik Guru dan Disiplin Belajar Melalui Motivasi Belajar Sebagai Intervening Terhadap Prestasi Belajar. Economic Education Analysis Journal. 4(1). 16-25.Patty, S., Wijono, S., & Setiawan, A. (2016). Hubungan Dukungan Sosial Teman Sebaya, Kontrol Diri, dan Jenis Kelamin dengan Prestasi Belajar Siswa di SMA Kristen YPKM Ambon. Psikodimensia, 15(2), 204-235.Prianto, A., & Putri, T. H. (2017). Pengaruh Ketersediaan Fasilitas Belajar, Dukungan Orang Tua yang Dirasakan Terhadap Motivasi dan Prestasi Belajar Siswa SMA PGRI Ngimbang Lamongan. Jurnal Pendidikan Ekonomi, Kewirausahaan, Bisnis, dan Manajemen (JPEKBM). 1(2). 13-38.Pratama, D. W., & Rusmawati, D. (2017). Hubungan Dukungan Sosial Teman Sebaya dengan Motivasi Belajar Dalam Program Sekolah Lima Hari di SMAN 5 Semarang. Jurnal Empati, 6 (4). 231-235.Putrie, C. A. R., & Fauzia, M. (2019). Pengaruh Dukungan Sosial Orang Tua terhadap Prestasi Belajar Siswa SMP Angkasa Halim Perdana Kusuma Jakarta Timur. Jurnal Inovasi Pendidikan Ekonomi. 9(2). 177-182.Purba, L. S., & Yilianto, J. E. (2019). Hubungan antara Regulasi Diri dan Prestasi Belajar pada Mahasiswa Perantau di Universitas X Surabaya. Psychopreneur Journal, 3(1), 16-25.Ramdhan, M. Y., & Harsono, L. D. (2015). Pengaruh Motivasi Belajar Terhadap Prestasi Belajar Mahasiswa Telkom University Program Pendidikan Jarak Jauh Tahun Akademik 2013/2014. e-Proceeding of Management. 2(1). 156-161.Suciani, D., & Rozali, Y. A. (2014). Hubungan Dukungan Sosial Dengan Motivasi Belajar Pada Mahasiswa Universitas Esa Unggul. Jurnal Psikologi.12 (2).Tayfurn, C., & Ulupinar, S. (2016). The Effect of Perceived Social Support on the Academic Achievement of Health College Students. Journal of Psychiatric Nursing. 7(1). 1-6.Tunggadewi, T. P., & Indriana, Y. (2017). Hubungan Antara Dukungan Sosial Dengan Motivasi Belajar pada Santri di Pesantren Tafidz Daarul Qur’an Jawa Tengah. Jurnal Empati, 7 (3). 313-317.Tinajero, et al. (2020). Preceived Social Support as a Predictor of Academic Success in Spanish University Student. Annalys of Psychology. 36(1). 134-142.Zulkarnain, M. (2019). Peranan Dukungan Sosial dan Self Esteem dalam Meningkatkan Motivasi Belajar. Dalam Diah & Purwandi, Prosding Seminar Nasional Magister Psikologi, (hlm. 447-452). Yogyakarta, Indonesia: Universitas Ahmad Dahlan.